Review on Tubing Corrosion in Oil and Gas Production Wells: Key Parameters, Prevention Strategies, Environmental Impact, and Future Perspectives - Mouneir, Samar M.; El-Shamy, Ashraf M. (Journal of Environmental Accounting and Management, 2026)
The review provides a comprehensive overview of the challenges associated with corrosion in pipelines used in the oil and gas industry. Corrosion poses a significant threat to the integrity and reliability of pipelines, leading to safety concerns, environmental hazards, and financial losses. This review synthesizes insights, prevention strategies, monitoring techniques, and future perspectives aimed at mitigating corrosion risks in oil and gas production pipelines. The review begins by elucidating the various forms of corrosion encountered in pipelines, including uniform corrosion, pitting corrosion, and stress corrosion cracking, among others. It explores the factors contributing to corrosion, such as the nature of the transported fluids, environmental conditions, and material properties, highlighting the complex interplay of factors that influence corrosion rates. Prevention strategies are then discussed, ranging from material selection and coating technologies to corrosion inhibitors and cathodic protection systems. The review evaluates the effectiveness of these strategies in mitigating corrosion and emphasizes the importance of implementing a multi-faceted approach to corrosion management. Monitoring techniques for detecting and assessing corrosion in pipelines are comprehensively reviewed, including non-destructive testing methods, online inspection tools, and corrosion monitoring sensors. The review highlights the advantages and limitations of each technique and emphasizes the importance of integrating multiple monitoring approaches to ensure accurate and timely corrosion detection. Finally, the review offers insights into future perspectives and emerging trends in pipeline corrosion management. It discusses advancements in predictive modeling, remote monitoring technologies, and the adoption of digitalization and artificial intelligence for proactive corrosion management. The review underscores the need for continued research and innovation to address evolving challenges and ensure the integrity and safety of oil and gas production pipelines.